Treatment of Effluent from the textile industry by adsorption on Clays and Photocatalytic Degradation - Gutarra Espinoza, Abel (2005)
In this work the treatment of textile efluentes by adsorption on clays and photocatalytic degradation are shown. The natural clay comes from Huancayo, Region Junin. After having purified, it was determined by diffraction and fluorescence techniques that it had a high montmorillonite percentage. Dyes used for the test of adsorption were direct-azo type, named red 80 and blue 71. Both dyes are frequently used in the production of textile. The acidactivation consisted on the partial dissolution of the clay in acid (HCI 2N) at 90°C in a reflux system. The structure and composition changes were analyzed by DRX, FRX and SEM. The results showed that the activated clay can increase its capacity of adsorption of dye textile in 30 times regarding the natural clay, reaching the equilibrium at 10-15 min. In this step, the concentration of blue dye down from 90 to 15 ppm in a reactor of IL of capacity with I g of clay. After adsorption, the clay was separated, then TiO, was added and the colloidal system was irradiated with ultraviolet light (UV). In this second step, dye remainder decrease slowlyup to reach less than 1 ppm.